Pemberian Serbuk Kelopak Rosella Merah yang Diseduh Mampu Mencegah Penurunan HDL Pada Sprague dawley yang Dipapar Jelantah - Arya Ulilalbab; Eni Maskanah (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Lipid metabolism disorder is caused by waste cooking oil that is one of the source of exogenous free radicals. Publics know the utilization of red rosella calyx is used as a brew that contains antioxidants. Purpose of this research is to find out the effect of giving brewed red rosella calyx to rat lipid metabolism caused by waste cooking oil on High-density Lipoprotein (HDL) value. This research used 24 male rats which were selected by random sampling and divided into 4 groups: positive control (2 ml kg/BW waste cooking oil given), negative control (without treatment), treatment 1 (2 ml/kg BW waste cooking oil given and giving of 540 mg/kg BW brewed red rosella calyx), and treatment 2 (2 ml/kg BW waste cooking oil given and giving of 810 mg/kg BW brewed red rosella calyx). One-way Analysis of Variance (α = 0.01) and Tukey honestly significant difference test showed that HDL p-value = 0.00. All groups have a significant effect on HDL. The best value is giving of 810 mg/kg BW dose of brewed red rosella calyx (HDL of 57.47 mg/dl). Giving of brewed red rosella calyx dose of 540 mg/kg BW (EC50 = 407.52 bpj) and red rosella calyx dose 810 mg/kg BW (EC50 = 247.82 bpj) can prevent HDL decrease. Red rosella calyx can improve the lipid profile of waste cooking oil treated to Sprague Dawley rats (especially for HDL on this research).